Determinan Tingkat Konsumsi Masyarakat Di Provinsi Sumatera Barat - Tasya Febsilia; Alpon Satrianto (Universitas Negeri Padang, 2026)
This study aims to analyze the factors influencing public consumption levels in West Sumatra Province. The variables used in this study include per capita income, savings, dependency ratio, health level, and education level. The data used is panel data from districts/cities in West Sumatra Province for the period 2015 to 2024. The analysis method used is panel data with a fixed effects model approach. The results show that per capita income and education level have a positive and significant effect on public consumption levels. Conversely, the dependency ratio and health level, as measured by the morbidity rate, have a negative and significant effect on consumption levels. Meanwhile, savings have a positive but insignificant effect on public consumption. Simultaneously, all independent variables significantly influence public consumption levels in West Sumatra Province. Keywords Consumption, per capita income, savings, dependency ratio, health level, education level.